Dietary adherence component of end-stage renal disease adherence questionnaire (ESRD-AQ): translation and validation - Karami, Sarah Muneera; Mohd Abu Bakar, Wan Azdie; Mat Ya, Roselawati; Sulaiman, Norhasmah (IIUM Press, 2024)
Introduction: A nutritionally balanced diet is crucial among end-stage renal disease (ESRD) patients to maintain their health status. An appropriate instrument is needed to assess ESRD patients’ adherence towards dietary recommendations. Several questionnaires to measure adherence behaviours of ESRD patients are available but none has ever been translated into the Malay language. Therefore, this study aimed to translate the End-stage Renal Disease Adherence Questionnaire (ESRD-AQ), focusing on the dietary adherence component, from English to Malay. Methodology: Forward and backward translations of the questionnaire were done involving experts in dietetics and linguistics to produce a pre-harmonized Malay translation and two backward English translations according to established guidelines. An expert committee reviewed these translated questionnaires to produce a harmonized version. This then underwent a pre-test and cognitive interview, as well as face validity assessment, involving 15 hemodialysis patients. The Cronbach’s alpha was also analyzed to assess the internal consistency of the questionnaire. Results: Minor amendments were made to several phrases during the expert committee review to ensure the translated questionnaire was contextually appropriate and culturally adapted in Malay language. All questions in the Malay version of ESRD-AQ achieved a Face Validity Index (FVI) value of 1.00, indicating high validity. Additionally, the questionnaire produced a Cronbach's alpha value of 0.84, which is within the acceptable range. Conclusion: The Malay version of ESRD-AQ (Dietary Adherence Component) underwent translation and validation protocols, the findings of which indicate that it is clear, comprehensible, and reliable for use in assessing dietary adherence among ESRD patients in Malaysia.